2010
DOI: 10.1016/j.nbd.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

D2 dopamine receptor subtype-mediated hyperactivity and amphetamine responses in a model of ADHD

Abstract: Low doses of psychostimulants produce beneficial behavioral effects in ADHD patients but the mechanisms underlying the response are not understood. Here we use the hyperactive mouse mutant coloboma to identify D2-like dopamine receptor subtypes that mediate the hyperactivity and response to amphetamine; we have previously demonstrated that D1-like dopamine receptors are not involved. Targeted deletion of the D2, but not the D3 or the D4, dopamine receptor in coloboma mice eliminated the hyperactivity; depletin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 65 publications
5
31
0
Order By: Relevance
“…These changes are very likely to affect the extent and balance in dopaminergic transmission mediated by the two dopamine receptor subtypes in striatonigral and striatopallidal neurons. Notably, in the Coloboma mouse model, the D2R has been proposed to mediate the effects linked to ADHD (38). Here we show that both D1R and D2R may be involved in the effects of CK1δ overexpression.…”
Section: Discussionmentioning
confidence: 58%
“…These changes are very likely to affect the extent and balance in dopaminergic transmission mediated by the two dopamine receptor subtypes in striatonigral and striatopallidal neurons. Notably, in the Coloboma mouse model, the D2R has been proposed to mediate the effects linked to ADHD (38). Here we show that both D1R and D2R may be involved in the effects of CK1δ overexpression.…”
Section: Discussionmentioning
confidence: 58%
“…Low levels of the availability of D 2 /D 3 receptors in the nucleus accumbens were found in impulsive rats (Dalley et al 2007). In the hyperactive mouse mutant coloboma, targeted depletion of the receptor D 2 resulted in the elimination of hyperactivity (Fan et al 2010). In humans, low D 2 /D 3 autoreceptor availability in the midbrain was shown to be associated with higher levels of trait impulsivity (Buckholtz et al 2010).…”
Section: Dopamine Receptorsmentioning
confidence: 99%
“…The SNAP-25 deficient coloboma mouse mutant that displays hyperkinetic behavior, as well as behavioral deficits reflecting inattention and impulsivity (Bruno et al, 2007; Hess et al, 1992; Hess et al, 1996) has been shown to fulfill the necessary criteria for a valid model of ADHD (Fan et al, 2012). Importantly, Hess and colleagues have shown that both the hyperactivity and amelioration of that hyperactivity by amphetamine exhibited by these mutant mice is D2R-dependent (Fan and Hess, 2007; Fan et al, 2010). Additionally, using microdialysis to assay dopamine efflux in freely moving mice, these investigators have demonstrated markedly increased basal levels of extracellular dopamine in striatum of this mouse model of ADHD that is further increased by amphetamine administration (Fan and Hess, 2007).…”
Section: 0 Discussionmentioning
confidence: 99%
“…This SNAP-25 deficient mouse, which exhibits a 50% reduction of SNAP-25 expression (Hess et al, 1992), displays certain hallmarks of ADHD including hyperactivity that is ameliorated by the psychostimulant amphetamine (Hess et al, 1996) as well as inattention and impulsivity (Bruno et al, 2007). Moreover, the hyperkinesis and amphetamine responsiveness of these mutants have been shown to be mediated through D2 dopamine receptors (Fan and Hess, 2007; Fan et al, 2010). Interestingly, the robust hyperactive behavior of this mutant appeared not to be recapitulated in heterozygote Snap25 null mutants (Washbourne et al, 2002), although it was recently reported that these mice do display more subtle behavioral deficits and a susceptibility to seizures (Corradini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%